The correlation between sarcopenia and osteoporosis in the elderly: a systematic review and meta-analysis - Jin, Sha; Zheng, Fengming; Liu, Huaili; Liu, Luping; Yu, Jie (Frontiers in Medicine, 2025)
BackgroundSarcopenia and osteoporosis, as two prevalent geriatric syndromes, synergistically elevate risks of falls, fractures, and disability in older adults. Despite shared pathophysiological mechanisms–including hormonal dysregulation, chronic inflammation, and attenuated mechanical loading. Existing studies have yet to establish consensus regarding the epidemiological association strength and interaction dynamics between sarcopenia and osteoporosis, particularly as heterogeneous characteristics–including sex, geographic region, and population subgroups–remain insufficiently characterized. This study aimed to quantitatively evaluate the sarcopenia-osteoporosis association in older adults through systematic review and meta-analysis of global observational studies, while analyzing the moderating effects of geographic location, sex, population characteristics, and diagnostic criteria on outcomes.MethodsWe searched PubMed, Embase, Cochrane Library, and China National Knowledge Infrastructure (CNKI) databases until September 2024. Fourteen observational studies quantifying muscle mass/function and bone mineral density were included. Two investigators independently performed literature screening and data extraction. Study quality was assessed using the Newcastle-Ottawa Scale (NOS). Studies were meta-analyzed by Review Manager 5.4 and Stata 17.0.ResultsA total of 14 studies (n = 182307) were included, and the meta-analysis showed that patients with sarcopenia had a significantly higher risk of osteoporosis (OR = 3.16, 95% CI: 2.47 to 4.02, p < 0.001). Subgroup analyses demonstrated an OR of 4.74 [3.19, 7.06] for osteoporosis in the male sarcopenia group compared to females (OR = 3.46; 95% CI, 2.50–4.78). Geographically, European populations exhibited the highest risk (OR = 4.37; 95% CI, 3.72–5.13), surpassing Asian (OR = 2.66; 95% CI, 1.74–4.07) and American cohorts (OR = 2.32; 95% CI, 1.54–3.49). Community-dwelling individuals showed greater susceptibility (OR = 3.70; 95% CI, 3.24–4.23) compared to inpatient and outpatient populations.ConclusionOur meta-analysis demonstrates that sarcopenia significantly elevates osteoporosis susceptibility, with heterogeneous risk profiles across geographic regions and population subgroups. However, limitations inherent to the methodological quality and sample size of included studies necessitate validation through large-scale prospective cohort investigations.